Adopting the ecovillage concept to shape a traditional bureaucratic village into a more sustainable community in Thailand. Issue 5 (20th October 2022) - Roongtawanreongsri, Saowalak; Boonkaew, Rachada
ABSTRACT: The ecovillage concept (EVC) is considered a promising path to sustainable living, particularly for developing countries. In this study we aimed to demonstrate the possibility of shaping a local bureaucratic village into a more sustainable community guided by the EVC. We explored the improvement of a community in Thailand six months after the EVC had been put into practice, drawing data from twenty-six community leaders and sixty-one household representatives using group discussions, participant observations, and interviews. The community capitals framework was used to highlight factors contributing to the improvement. The results show that the transformation is potentially possible. We recommend that relevant organizations with a similar goal should start with communities that possess endogenous qualities and provide education about the EVC as a foundation. Critical factors that contribute highly to the achievement of sustainable communities are human, social and cultural capital.